2020
DOI: 10.1063/1.5141813
|View full text |Cite
|
Sign up to set email alerts
|

Multicatalytic behavior of Ba0.85Ca0.15Ti0.9 Zr0.1O3 ceramics for pharmaceutical/dye/bacterial treatments

Abstract: Multicatalytic activities (photocatalysis, piezocatalysis, and pyrocatalysis) of ferroelectric ceramics Ba0.85Ca0.15Ti0.9Zr0.1O3 (BCZTO) were studied. Maximum degradations (89% and 81%) were achieved in piezo-photocatalytic experiments for degradation of Rhodamine B (RB) and ciprofloxacin. Similarly, 95% degradation of RB was achieved during pyrocatalysis in 250 heating/cooling cycles. Antibacterial performance of ceramics was analyzed with the help of Gram-positive and Gram-negative bacteria-killing processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Furthermore, the potential benefits of an electric poling procedure on the catalytic activity of pyrocatalysts were ignored with few exceptions. 23,30,31 This is remarkable, since several studies of the related piezocatalysis have shown a strong increase of piezocatalytic activity through such a remanent alignment of ferroelectric dipoles inside ferroelectric particles. [32][33][34] In this work, the influence of the particle size on the pyrocatalytic activity of BaTiO 3 powder (BT) catalysts containing nanoparticles with nominal particle sizes of 100, 200 and 500 nm was investigated.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the potential benefits of an electric poling procedure on the catalytic activity of pyrocatalysts were ignored with few exceptions. 23,30,31 This is remarkable, since several studies of the related piezocatalysis have shown a strong increase of piezocatalytic activity through such a remanent alignment of ferroelectric dipoles inside ferroelectric particles. [32][33][34] In this work, the influence of the particle size on the pyrocatalytic activity of BaTiO 3 powder (BT) catalysts containing nanoparticles with nominal particle sizes of 100, 200 and 500 nm was investigated.…”
Section: Introductionmentioning
confidence: 94%
“…21 However, there is a great gap in knowledge about the exact catalytic mechanism as well as the influence of essential process/reaction/material parameters on the pyrocatalytic activity. In recent years, various experimental and some theoretical studies investigated the catalytic potential of pyroelectric materials for water remediation (disinfection, 20 micropollutant degradation 22,23 ) but also for hydrogen generation through water splitting. [24][25][26] Several studies introduced new pyrocatalysts (LiNbO 3 , LiTaO 3 , BaTiO 3 , BiFeO 3 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is a challenge to use piezoelectric energy harvesters for large scale applications 6,7 . Piezocatalysis is one of the emerging fields where piezoelectric materials participate in catalytic reactions for organic pollutant degradations 8‐11 . This is a kind of coupling among mechanical‐electrical‐chemical fields and was observed particularly in non‐centrosymmetric semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Till now, countable articles have been reported in this direction and there is various aspects which need to be explored 5 . Some of the unexplored issues are quantitative role of piezoelectric nature, role of semiconductor nature, and effectiveness of piezocatalytic for degradation of various organic pollutant such as bacterial cell, dyes, pharmaceuticals etc 10‐12 . Most of the recent studies have reported piezocatalysis using BaTiO 3 , Sr 0.7 Ba 0.3 Nb 2 O 6 , Bi 4 Ti 3 O 12 , LiNbO 3 , K 0.5 Na 0.5 NbO 3 , Bi 0.5 Na 0.5 TiO 3, Pb(Zr,Ti)O 3 , Ba 0.85 Ca 0.85 Ti 0.90 Zr 0.10 O 3 (BCZTO), and ZnO 13‐21 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Some of the unexplored issues are quantitative role of piezoelectric nature, role of semiconductor nature, and effectiveness of piezocatalytic for degradation of various organic pollutant such as bacterial cell, dyes, pharmaceuticals etc. [10][11][12] Most of the recent studies have reported piezocatalysis using BaTiO 3 , Sr 0.7 Ba 0.3 Nb 2 O 6 , Bi 4 Ti 3 O 12 , LiNbO 3 , K 0.5 Na 0.5 NbO 3 , Bi 0.5 Na 0.5 TiO 3, Pb(Zr,Ti)O 3 , Ba 0.85 Ca 0.85 Ti 0.90 Zr 0.10 O 3 (BCZTO), and ZnO. [13][14][15][16][17][18][19][20][21] Among these, BaTiO 3 is the simplest, traditional, and important ferroelctric ceramics.…”
Section: Introductionmentioning
confidence: 99%